Genomic Analysis of Putative Virulence Factors Affecting Cytotoxicity of Cronobacter - Cui, Jinghua; Hu, Jinrui; Du, Xiaoli; Yan, Chao; Xue, Guanhua; Li, Shaoli; Cui, Zhigang; Huang, Hua; Yuan, Jing (Frontiers in Microbiology, 2020)
Cronobacter spp. can cause systemic infections in immunocompromised patients, especially neonatal meningitis, sepsis, and necrotizing enterocolitis in neonates. Although some virulence factors have been reported previously, the pathogenesis of Cronobacter remains unclear. In this study, we compared genome sequences of Cronobacter from different species, sequence types, and sources, with the virulence genes in the virulence factor database (VFDB). The results showed that Cronobacter has species-specificity for these virulence genes. Besides this, the two gene clusters, including sfp encoding fimbriae and hly encoding hemolysin, were discovered. Through cell adhesion, cytotoxicity, and hemolysis assay, we found the isolates possessed the two gene clusters, had higher cytotoxicity and stronger hemolysis capacity than other isolates in this study. In addition, Type VI secretion system (T6SS) cluster and putative fimbria gene clusters of Cronobacter were analyzed, and T6SS have species-specificity, and that isolates with high cytotoxicity possessed more complete T6SS cluster construction than the rest. It demonstrated the two novel gene clusters and T6SS cluster were involved in the mechanism underlying the cytotoxicity of Cronobacter.